Release of VAMP5‐positive extracellular vesicles by retinal Müller glia in vivo. Issue 9 (31st August 2022) - Demais, Valerie; Pohl, Anne; Wunderlich, Kirsten A.; Pfaller, Anna M.; Kaplan, Lew; Barthélémy, Amelie; Dittrich, Robin; Puig, Berta; Giebel, Bernd; Hauck, Stefanie M.; Pfrieger, Frank W.; Grosche, Antje
Abstract: Cell‐cell interactions in the central nervous system are based on the release of molecules mediating signal exchange and providing structural and trophic support through vesicular exocytosis and the formation of extracellular vesicles. The specific mechanisms employed by each cell type in the brain are incompletely understood. Here, we explored the means of communication used by Müller cells, a type of radial glial cells in the retina, which forms part of the central nervous system. Using immunohistochemical, electron microscopic, and molecular analyses, we provide evidence for the release of distinct extracellular vesicles from endfeet and microvilli of retinal Müller cells in adult mice in vivo. We identify VAMP5 as a Müller cell‐specific SNARE component that is part of extracellular vesicles and responsive to ischemia, and we reveal differences between the secretomes of immunoaffinity‐purified Müller cells and neurons in vitro. Our findings suggest extracellular vesicle‐based communication as an important mediator of cellular interactions in the retina.